Provable secure digital watermarking scheme (Tongxin xuebao)
A novel provable security watermarking scheme was presented by adopting the digital watermarking technol-ogy,cryptology and encode method,it comprises embedding watermarks scheme and detecting watermarks scheme.The participant ID,Hash of the digital work and watermarking keys are regarded as the watermarks in the scheme,so that the watermarks can be used to authenticate lawful user and judge the ownership.The scheme has rigorously security almost against all watermarks protocol attacks.Especially,it has correct ability,as so as higher efficiency.